Environmental dike design considerations for the Lower Mississippi River - Eom, Moosub, author; Watson, Chester, advisor; Grigg, Neil S., committee member; Bledsoe, Brian P., committee member; Wohl, Ellen E., committee member (Colorado State University. Libraries, 2004)
The purpose of the Lower Mississippi River dike system is to maintain required minimum navigation channel width and depth. In recent years, it is known that the dike structures, and the topographic features and fluvial landforms associated with dike systems, constitute a distinct aquatic habitat in the Lower Mississippi River ecosystem. However, in spite of a variety of economic and environmental benefits from dikes, no definitive hydraulic design criteria have been developed. This is primarily due to the wide range of variables affecting the performance of the dikes and the varying importance of these variables with specific applications. To optimize dike design, including dredging-free navigation channels and aquatic habitat within the dike pool area, it is very important to predict the actual river responses to dike installation. Therefore, the primary objective of this study is to suggest optimal design guidance for the dike system based on statistical and numerical methods using the data sets collected from the Lower Mississippi River dike systems. Linear regression analysis was performed, to find relationships between dike geometric parameters (dike length, elevation, radius of curvature of the reach, etc.) and pool surface area change, which is considered the dike pool parameter most highly correlated with dike geometric parameters. It was shown that the shorter and the lower the dike, the less the pool surface area decreases, thereby preserving more habitat area. Two kinds of multiple regression model equations were suggested; one consisting of measured parameters and the other consisting of dimensionless parameters, both of which can be used to predict the pool habitat area change represented by the pool surface area change for the given dike and channel geometry. A HEC-6 model was used, to find relationships between dike geometric parameters and main channel parameters such as thalweg elevation depth or cross-section area. The simulated cross-section areas matched relatively well with the measured. The effect of each dike geometric parameter on thalweg elevation was predicted. It was found that the effect of the dike length on thalweg elevation is much greater than that of dike elevation. It is expected that the HEC-6 model can be used to evaluate the scenarios established at the initial stage of dike design, which are possible combinations of the dike geometric parameters satisfying the master plan for the waterway project. The Physical HABitat SIMulation (PHABSIM) model, a software package used in the Instream Flow Incremental Methodology (IFIM), was used to predict the usable habitat area of each life stage of the representative fish (target species) within the dike field. It was shown that the dike pool surface area change can represent the aquatic habitat change for fish living in the dike field. It was also shown that cross-section geometry data calculated from the HEC-6 model can be used as input geometry data for the PHABSIM model, to predict change in aquatic habitat for fish, although there is a tendency to underestimate the usable habitat area. Finally, procedures for environmental dike design were suggested, based on the results obtained from these analyses.
Keywords: civil engineering; environmental engineering